Dr. K.C. Mehta and Manoranjan Mitra Memorial Lecture Award (2004) - A critical appraisal of seed health certification and transboundary movement of seeds under WTO regime - R.K. KHETARPAL - KHETARPAL, R.K. (Indian Phytopathology, 2004)
It is well known that about 90% of all food crops grown in the world are propagated by seed.* Seeds also constitute the major agricultural commodity for trade. Production and distribution of high quality wheat seed has been attributed as one of the important factors in sustaining the green revolution in India (Nagarajan, 2004). During 1960s spectacular growth was witnessed in the seed industry with lead provided by the National Seeds Corporation (NSC) Ltd. in quality seed production (Bhatia, 2004). However, the quality control from seed health point of view has never received due importance. Besides, with increasing globalization of agricultural markets, removal of trade barriers and the trend for seed companies to amalgamate, forging large multinational companies, the production and movement of commercial quantities of seeds across and within countries have increased (Nagarajan and Khetarpal, 2004). With this, the accompanying risk of introducing exotic diseases through imports has increased manifold. However, the neglect of seed health component in the national seed certification programme and trade is indeed a paradox given the fact that, in ancient (400 BC) and medieval India, substantial knowledge was generated on the importance of seed health (Nene, 1999).